Efficient Frequency Conversion with Geometric Phase Control in Optical Metasurfaces. Issue 12 (20th February 2022) - Reineke Matsudo, Bernhard; Sain, Basudeb; Carletti, Luca; Zhang, Xue; Gao, Wenlong; de Angelis, Costantino; Huang, Lingling; Zentgraf, Thomas
Abstract: Metasurfaces have appeared as a versatile platform for miniaturized functional nonlinear optics due to their design freedom in tailoring wavefronts. The key factor that limits its application in functional devices is the low conversion efficiency. Recently, dielectric metasurfaces governed by either high‐quality factor modes (quasi‐bound states in the continuum) or Mie modes, enabling strong light–matter interaction, have become a prolific route to achieve high nonlinear efficiency. Here, an effective way of spatial nonlinear phase control by using the Pancharatnam–Berry phase principle with a high third harmonic conversion efficiency of 10 −4 W −2 is demonstrated both numerically and experimentally. It is found that the magnetic Mie resonance appears to be the main contributor to the third harmonic response, while the contribution from the quasi‐bound states in the continuum is negligible. This is confirmed by a phenomenological model based on coupled anharmonic oscillators. Besides, the metasurface provides experimentally a high diffraction efficiency (80%–90%) in both polarization channels. A functional application of this approach is shown by experimentally reconstructing an encoded polarization‐multiplexed vortex beam array with different topological charges at the third harmonic frequency with high fidelity. The approach has the potential viability for future on‐chip nonlinear signal processing and wavefront control. Abstract : An effective solution for the nonlinear generation and manipulation of light at the nanoscale is presented by tailoring the nonlinear‐phase simultaneously at a very high conversion efficiency, which is imperative for the high‐fidelity realization of any nonlinear optical functionality. The concept of geometric‐phase is efficiently combined with the spatial electromagnetic modes in silicon metasurface for robust manipulation of the third‐harmonic phase and practical realization of nonlinear vortex arrays at a conversion efficiency 10 −4 W −2 .